EVALUASI SISTEM STANDAR MUTU PENDIDIKAN KEPELAUTAN INDONESIA PROGRAM STUDI NAUTIKA DI AKADEMI MARITIM DJADAJAT - Tukiyo, - (Jurnal Ilmiah Widya, 2014)
Nowadays quality and competitiveness as well as an index of the achievements of the graduates the Academy of Maritime in Indonesia is still low. The Government of Indonesia in 2003 has set the standard for quality Maritime System to be implemented in Indonesia's maritime education in Indonesia. This study aims to measure the effectiveness of, and to know the factors supporting factors, and a barrier to the implementation of a standard system of quality Maritime on nautical Maritime Academy courses Djadajat. This research uses evaluation approach to SWOT analysis system. The results showed that: (1) the level of effectiveness of implementation of a standard system of quality Maritime on Nautical Maritime Academy Courses Djadajat, quantitatively has reached 83%. (2) supporting factor, namely: (a) courses have had the vision, mission, goals are clear and realistic and (b) have qualified human resources, faculty and administrative staff are experienced prosesional,(c) implementing competency-based curriculum that is recognized internationally, (d) graduates desperately needed job market in the field of domestic and foreign shipping, (e) opportunities to work in the field of commercial shipping is very open.(3) the factors restricting namely: (a) Not all staff understand the vision, mission and objectives of the program of study, and standard operational procedures (SOP) (b) Coordination, communication and cooperation between work units have not been optimal, (c) the development of human resources is still limited due to the limited funds.